Development of Consistency Personality Measurement Instruments on Students at SMA Dwijendra Bualu - Ni Komang Shintia Agustini Purnama Sari; Ni Ketut Suarni; Nyoman Dantes (Department of Guidance and Counseling, FIP, Undiksha, 2021)
This research is a type of research and development. Measurement of personality consistency was carried out by testing the validity of the instrument items by applying the product moment correlation formula and testing the reliability of the questionnaire with Cronbach's Alpha coefficient. Based on the VC calculation on the content validation test with the Gregory formula, the results are 1 or > 0, it is stated that the personality consistency character instrument is very valid. The results of data analysis conducted to determine the validity of items using the product moment formula obtained 39 items declared valid or very good. Based on these results, it is expected that students are able to develop personality consistency so that they have goals and efforts or continuous development, this is still needed even though they have succeeded in achieving their goals in life.